The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18203/2319-2003.ijbcp20171656
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metformin on ECG, HR and BP of rats administered with cardiotoxic agent doxorubicin

Abstract: Background: Cardiovascular complications during drug therapy is worrisome and has been known to increase morbidity and mortality. The aim of this study was to investigate the effect of metformin on BP, HR, and ECG, after subacute administration of doxorubicin in rats.Methods: Laboratory acclimatised animals were divided into 4 experimental groups consisting of group I as the control, given 0.5ml normal saline. Group II, received 3mg/kg doxorubicin on alternate days, while group III was given 300mg/kg metformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…An analysis of the length of the PR interval is crucial in the diagnosis of atrioventricular blocks. The PR interval was reported to increase with DOX [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the length of the PR interval is crucial in the diagnosis of atrioventricular blocks. The PR interval was reported to increase with DOX [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prolonged QT interval is considered a useful indicator of the drug-induced cardiotoxicity [ 56 , 57 ]. Many studies have revealed QT prolongation produced by DOX [ 46 , 47 , 58 , 59 ]. It is well established that QT interval lengths depend on the heart rate (HR).…”
Section: Discussionmentioning
confidence: 99%
“…The experiment provides baseline recording lasting for 15 min, followed by a recording session of 45 min during/after vehicle or drugs exposure. For data acquisition, a series of repeated measurements were performed on the same animal at each time point, and data for the same animal were collected over the different week intervals [ 129 , 130 ].…”
Section: Methodsmentioning
confidence: 99%
“…In cardiac insufficiency, myocardial ischemia, and right and left bundle branch blockages, the big QRS complex shows ventricular rhythms as well as abnormalities in intraventricular conduction. In doxorubicin-treated rats, wide QRS complexes were seen [55]. Due to cancelations and decreased electromotive force generation, several myocardial infarctions have been associated with a reduction in the amplitude of QRS complexes [56][57][58].…”
Section: Discussionmentioning
confidence: 99%